The Type of Control Deficiency, Internal Audit Function Relationship and Internal Auditor’S Evaluation: an Experimental Study - Fadhila, Lyra Raisa; Islami, Imas Nurani (Jurnal Akuntansi dan Bisnis, 2019)
This study aims to examine whether the type of internal control deficiency and the two parties that have a relationship with internal audit function influence the internal control evaluation by internal auditors. This study was conducted a behavioral experiment methodology in 2x2 between-subjects factorial design, and internal auditor as a participant. This study proved that there is an influence between the type of deficiency and the internal auditor’s evaluation. In contrast, this study could not prove the effect of the internal audit function relationship toward auditor’s evaluation of process-specific deficiency. This study has a great implication on internal control over financial reporting) in every part of the company. The limitation of this study is the findings are not generalizable beyond the internal control scenario depicted in the case materials. This study encourages future research to examine the usefulness of the role of the external auditor, and other parties charged with corporate governance, in mitigating any bias from this study.  Penelitian ini bertujuan untuk menguji apakah jenis penyimpangan pengendalian internal dan pihak yang memiliki hubungan dengan audit internal memengaruhi evaluasi audit internal terhadap pengendalian internal. Penelitian ini menggunakan metode penelitian eksperimen perilaku yang dikemas dalam desain faktorial antara subjek 2x2, dengan auditor internal sebagai subjek. Penelitian ini dapat membuktikan adanya pengaruh jenis penyimpangan terhadap evaluasi pengendalian. Di sisi lain, penelitian ini tidak dapat membuktikan pengaruh pihak yang memiliki hubungan dengan IAF terhadap evaluasi penyimpangan pengendalian proses-spesifik. Studi ini memiliki implikasi yang besar terhadap pengendalian internal pada laporan keuangan di seluruh perusahaan. Limitasi dari studi ini adalah kurangnya generalisasi temuan di luar skenario pengendalian internal yang digambarkan dalam materi kasus. Studi ini juga memotivasi penelitian selanjutnya untuk menguji peran auditor eksternal dan pihak lain yang bertanggung jawab atas tata kelola perusahaan dalam mengurangi bias dari penelitian ini.